The Beguines of Medieval Świdnica : The Interrogation of the ""Daughters of Odelindis"" In 1332. - Kras, Paweł (Heresy and inquisition in the Middle Ages., 2023)
Documents recording the interrogation of sixteen women and the nature of their unusual spiritual practices, now available in a full edition and, for the first time, a full English translation.